How to survive in anaesthesia a guide for trainees - Robinson, Neville; Fawcett, William 1962-; Hall, George M. (George Martin) (Cambridge medicine (Series), 2017)
The first few months as a trainee anaesthetist are a daunting prospect, filled with new information, skills and terminology. This concise reference, now in its fifth edition, provides doctors with a clear introduction to the practice. Fully updated and split into four key parts for quick consultation, the reader can recap on the airway and anaesthetic equipment, and find crucial advice on crises such as cardiac arrest, haemorrhage and blood transfusion. Part III focuses on subspecialties, with new chapters on obstetric anaesthesia, common regional nerve blocks, and laparoscopy, while the newly added fourth part provides information on intensive care and peri-operative medicine. Written in an accessible and often humorous style, How to Survive in Anaesthesia is an essential resource in learning the safe fundamentals of the practice for trainee anaesthetists, as well as operating department practitioners, physicians' assistants and anaesthetic nurses